Mapping uranium concentration in soil: Belgian experience towards a European map. (January 2017) - Cinelli, Giorgia; Tondeur, Francois; Dehandschutter, Boris; Bossew, Peter; Tollefsen, Tore; De Cort, Marc
Abstract: A map of uranium concentration in soil has been planned for the European Atlas of Natural Radiation. This Atlas is being developed by the Radioactivity Environmental Monitoring (REM) group of the Joint Research Centre (JRC) of the European Commission. The great interest in uranium compared to other terrestrial radionuclides stems from the fact that radon ( 222 Rn) is in the decay chain of uranium ( 238 U) and that public exposure to natural ionizing radiation is largely due to indoor radon. With several different databases available, including data (albeit not calibrated) from an airborne survey, Belgium is a favourable case for exploring the methodology of uranium mapping. A harmonized database of uranium in soil was built by merging radiological (not airborne) and geochemical data. Using this harmonized database it was possible to calibrate the data from the airborne survey. Several methods were used to perform spatial interpolation and to smooth the data: moving average without constraint, by soil class and by geological unit. When using the harmonized database, it is first necessary to evaluate the uranium concentration in areas without data or with an insufficient number of data points. Overall, there is a reasonable agreement between the maps on a 1 km × 1 km grid obtained with the two datasets (airborne U and harmonized soil U) with all the methods. The agreement is better when the maps are reduced to a 10 km × 10 km grid; the latter could be used for the European map of uranium concentration in soil. Highlights: Harmonized soil U database built merging radiological (no airborne) and geochemical data. U airborne map calibrated using the harmonized U soil database. Mapping methods: moving average without constraint, by soil class and by geological unit. Agreement between the maps obtained with the airborne U and soil U with all the methods. Maps are reduced to a 10 × 10 km 2 grid to be used for the European map of U in soil.